Translation of Evidence into Practice: Revisiting Essential Newborn Care Study Outcomes - Upul Senarath (College of Community Physicians of Sri Lanka, 2021)
Professor Dulitha Nandanie Fernando (1944-2021) is much recognized for her contribution to high-quality research that generated evidence for public health policy and practice in Sri Lanka. The present article is one such example of her contribution to the translation of evidence into practice in maternal and child health. The article aims to demonstrate how the knowledge generated through a study conducted on essential newborn care in Sri Lanka during 2003-04 period enriched the global evidence base and impacted the newborn care programme and services in Sri Lanka.